Nursing Care for N with Bronchopneumonia in RSPPN Inpatient Room: A Case Study Report - Ana Fauziah; Herlina (Journal of Applied Holistic Nursing Science, 2025)
Background: Bronchopneumonia is an infection of the lower respiratory tract caused by bacteria, viruses, or fungi. Children are more susceptible to Bronchopneumonia because their immune systems are weak. Bronchopneumonia can cause complications such as emphysema, acute otitis media, atelectasis, emphysema, and meningitis if not treated immediately. This study aims to implement Nursing Care for patient An. N with bronchopneumonia in the Inpatient Room of RSPPN Panglima Besar Soedirman. Research Methods: This study aimed to evaluate the effectiveness of This study is a case study of pediatric nursing focusing on one case of Bronchopneumonia, which includes assessment, diagnosis, intervention, implementation, and evaluation. Results: The study showed nursing diagnoses including ineffective airway clearance related to airway hypersecretion, hyperthermia related to the disease process, risk of falling related to having fallen, and knowledge deficit related to lack of exposure to information. Nursing implementation was carried out according to problem priorities for 3x24 hours. Implementation of independent nursing care for ineffective airway clearance problems, patients underwent chest physiotherapy and positioning, there was improvement although complaints still existed, so the problem was partially resolved. The diagnosis of hyperthermia, risk of falling, and knowledge deficit were successfully resolved. Conclusion: Nursing care effectively improves bronchopneumonia patients’ condition through chest physiotherapy, positioning, and targeted family education.